2020
DOI: 10.1073/pnas.1912429117
|View full text |Cite
|
Sign up to set email alerts
|

Central neurogenetic signatures of the visuomotor integration system

Abstract: Visuomotor impairments characterize numerous neurological disorders and neurogenetic syndromes, such as autism spectrum disorder (ASD) and Dravet, Fragile X, Prader–Willi, Turner, and Williams syndromes. Despite recent advances in systems neuroscience, the biological basis underlying visuomotor functional impairments associated with these clinical conditions is poorly understood. In this study, we used neuroimaging connectomic approaches to map the visuomotor integration (VMI) system in the human brain and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…Recently, normative values have been provided to help occupational therapy practitioners 11 . It is known that compromised ability to interactively coordinate visual perception and fine motor skills has been associated with a variety of neurological disorders and neurogenetic syndromes 12 . In elderly drivers who have suffered a stroke, psychomotor abilities such as visual information processing and allocation of attentional resources are degraded.…”
mentioning
confidence: 99%
“…Recently, normative values have been provided to help occupational therapy practitioners 11 . It is known that compromised ability to interactively coordinate visual perception and fine motor skills has been associated with a variety of neurological disorders and neurogenetic syndromes 12 . In elderly drivers who have suffered a stroke, psychomotor abilities such as visual information processing and allocation of attentional resources are degraded.…”
mentioning
confidence: 99%
“…Our main result is that we found an enrichment associated with biological processes related to cholesterol and other lipoproteins for one of the ASD subtypes, with an enrichment above 100-fold in some cases. To the best of our knowledge, such a high enrichment has yet to be reported in any previous studies using AHBA, neither in studies assessing myelination (73), hierarchical cortical organization (74), visuomotor integration (47), nor in studies of large-scale connectivity (45,75,76). It is exceptionally important to highlight that if enrichment is carried out on the entire autistic population, without previously performing any subtyping, this association with cholesterol is masked, such that the process of subtyping is really critical to find such an enrichment.…”
Section: Discussionmentioning
confidence: 82%
“…Here, we take a step forward and ask if it is possible to perform a correspondence analysis between the large-scale connectivity patterns and the Allen Human Brain Atlas (AHBA) of whole-brain transcriptional data (44) for each ASD subtype, following a similar methodology to that used previously (45)(46)(47). Our hypothesis is that by identifying the genes whose expression maps coincide more closely with the connectivity maps, we might better understand the neurogenetic signature and neurobiological mechanisms associated with each subtype of ASD, a major challenge in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 106 high-risk infants, the 15 that went on to meet diagnostic criteria for ASD at 24 months displayed hyperexpansion of the cortical surface between 6 and 12 months of age, followed by a brain volume overgrowth between 12 and 24 months [ 82 ]. Further, a recent study has found that the expression of TBR1 overlaps with that of visuomotor integrators in the visual and motor cortices, showing the relevance of gene expression co-regulation at a circuit level [ 83 ].…”
Section: Asd Risk Converging On Cortical Development—evidence Frommentioning
confidence: 99%